2016
DOI: 10.1002/ijc.30149
|View full text |Cite
|
Sign up to set email alerts
|

Causes and outcomes of emergency presentation of rectal cancer

Abstract: Emergency presentation of rectal cancer carries a relatively poor prognosis, but the roles and interactions of causative factors remain unclear. We describe an innovative statistical approach which distinguishes between direct and indirect effects of a number of contextual, patient and tumour factors on emergency presentation and outcome of rectal cancer. All patients diagnosed with rectal cancer in Ireland 2004-2008 were included. Registry information, linked to hospital discharge data, provided data on patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
(69 reference statements)
3
19
0
Order By: Relevance
“…In oncology, a study of colorectal cancer patients26 showed that inadequate functional health literacy was more frequently observed in patients with age over 65 years. An interesting finding was observed in a large study of 2,750 colorectal cancer patients in Ireland:27 older patients were more likely to have an emergency presentation, analogous to UPS in that study, and emergency patients had worse clinical outcomes. Age is also relevant in determining the focus of educational areas for oncology patients,16 and delivering education to more elderly patients is feasible.…”
Section: Discussionmentioning
confidence: 66%
“…In oncology, a study of colorectal cancer patients26 showed that inadequate functional health literacy was more frequently observed in patients with age over 65 years. An interesting finding was observed in a large study of 2,750 colorectal cancer patients in Ireland:27 older patients were more likely to have an emergency presentation, analogous to UPS in that study, and emergency patients had worse clinical outcomes. Age is also relevant in determining the focus of educational areas for oncology patients,16 and delivering education to more elderly patients is feasible.…”
Section: Discussionmentioning
confidence: 66%
“…Tumor specific biology has been linked to increased associations with emergent presentations, with more rapidly, aggressive tumors being more likely to be diagnosed emergently. 35 Regardless, we made an inference that being diagnosed with cancer within 6 months of a recorded ED visit, meant those ED physicians had an opportunity to diagnose asymptomatic cancer, if that ED visit wasn’t directly related to the presentation of emergent cancer diagnosis. Further, no knowledge is known about previous screenings and primary care follow up, thus no inference can be made to know whether or not screening may have reduced the likelihood of the found associations.…”
Section: Discussionmentioning
confidence: 99%
“…According to epidemiological studies, low residue diet, high fat diet, benign adenoma (papillary adenoma and familial multiple polyposis) cancer are all risk factors in rectal cancer. [10,11] The pathogenesis of rectal cancer is usually considered to be influenced by both the diet and environment and its mechanism has not yet been completely determined.…”
Section: Discussionmentioning
confidence: 99%